TREATMENT OF TEXTILE DYEING INDUSTRY EFFLUENT USING COAGULATION TECHNIQUE - ASHOK KUMAR POPURI; HEMALATHA.V. ADAPA; BANGARAIAH PAGALA (International Journal of Pharma and Bio Sciences, 2015)
Dyes are colouring compounds being extensively used in textile industries and the indiscriminate disposal of dye wastewater poses one of the major problems on the environment. This effluent contains a variety of contaminants viz. nature of acidic, caustic, dissolved solids and toxic compounds. The micro toxins are developed due to colouring agents by forming chelating under suitable chemical environment. The objective of the present work is to investigate the effectiveness of chemical treatment on removal of colour of simulated acid dye solutions. Three dye stuffs belonging to acid group were employed and batch tests were conducted with three coagulants (Calcium hydroxide, Ferric sulphate and Aluminium chloride) to access feasibility and also to study the optimum values for coagulant dosage, RPM, pH and time. The study clearly indicates that effluent-1 responds effectively to ferric sulphate, effluent-2 responds effectively to aluminium chloride and effluent-3 is moderately responded to calcium hydroxide.